2008
DOI: 10.1017/s0016672307009081
|View full text |Cite
|
Sign up to set email alerts
|

The effect of a barrier to gene flow on patterns of geographic variation

Abstract: SummaryExplicit formulae are given for the effects of a barrier to gene flow on random fluctuations in allele frequency; these formulae can also be seen as generating functions for the distribution of coalescence times. The formulae are derived using a continuous diffusion approximation, which is accurate over all but very small spatial scales. The continuous approximation is confirmed by comparison with the exact solution to the stepping stone model. In both one and two spatial dimensions, the variance of flu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
39
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(41 citation statements)
references
References 34 publications
1
39
0
Order By: Relevance
“…LDD does not influence the F ST distribution within a patch (Figure 6), where there are no barriers to dispersal and the sampled demes will likely be part of the same sectors (being close to each other). Our findings are consistent with the simulation study of Wegmann et al (2006) and the theoretical results of Barton (2008), where an increase in the variance of F ST was observed in the presence of spatial heterogeneity or dispersal barriers.…”
Section: Influence Of Lddsupporting
confidence: 92%
“…LDD does not influence the F ST distribution within a patch (Figure 6), where there are no barriers to dispersal and the sampled demes will likely be part of the same sectors (being close to each other). Our findings are consistent with the simulation study of Wegmann et al (2006) and the theoretical results of Barton (2008), where an increase in the variance of F ST was observed in the presence of spatial heterogeneity or dispersal barriers.…”
Section: Influence Of Lddsupporting
confidence: 92%
“…For a population occupying a linear habitat, Nagylaki (1988) derived continuous equations for identity by state by taking the limit of a model of linear demes that exchange migrants (the so called stepping stone model). Barton (2008) expanded this by solving an analogous equation for two-dimensional populations. His formulas are given as a numerical Fourier transform that diverges for nearby individuals.…”
Section: Modelmentioning
confidence: 99%
“…His formulas are given as a numerical Fourier transform that diverges for nearby individuals. These equations for two-dimensional populations are formally problematic, as they were not obtained by rescaling (which is impossible in two spatial dimensions), but Barton (2008) demonstrated that the solution is in close agreement with the solutions from a discrete stepping stone model for all but very close distances.…”
Section: Modelmentioning
confidence: 99%
See 2 more Smart Citations